Fetal Echocardiography Audit in a Tertiary Hospital in Ibadan, Nigeria - Adebayo BE; Akinmoladun JA; Agaja OT (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
Background: Delayed detection of congenital heart diseases in low- and middle-income countries (LMICs) contributes to the poor outcome of infants with cardiac anomalies. Fetal echocardiography (FE) can detect heart defects in-utero as early as the 18th gestational week (GA), giving parents and medical professionals time to prepare for the baby's delivery and appropriate treatment. University College Hospital, Nigeria, is one of the few centres in Nigeria where FE is performed. Objectives: To examine the indications for referral for FE and the diagnoses made in our first four years of performing FE. Methods: FE was performed in the antenatal clinic of the University College Hospital, Ibadan, Nigeria, using the GE Voluson P6 machine with a 2-6-RS probe. Demographic information was obtained from the antenatal clinic records of the women who had FE using a semi-structured questionnaire. FE diagnoses were retrieved from the FE register. Results: A total of 129 women whose records were available were recruited for this study. The mean age of the women was 31.7±5.5 years. Forty-two women (32.6%) were referred because of echogenic foci, making this the most common indication for FE. Twenty-nine (22.5%) fetuses had structural heart defects, the most common being Ventricular Septal Defect. Conclusion: There is a need for Obstetricians and Paediatricians to be aware of the indications for fetal echocardiography and refer women appropriately.